High interferon‐stimulated gene ISG‐15 expression affects HCV treatment outcome in patients co‐infected with HIV and HCV. Issue 6 (12th April 2013) - Katsounas, Antonios; Hubbard, Jonathan J.; Wang, Crystal H.; Zhang, Xiaozhen; Dou, Diana; Shivakumar, Bhavana; Winter, Sophie; Schlaak, Joerg F.; Lempicki, Richard A.; Masur, Henry; Polis, Michael; Kottilil, Shyam; et al.
Abstract: Increased baseline expression and lack of induction of interferon‐stimulated genes (ISG) are strong negative predictors of therapeutic response to PegIFN/RBV in patients co‐infected with HIV and hepatitis C virus (HCV). This study specifically addressed whether ISG‐15 expression influences therapeutic responses in 20 HIV/HCV genotype‐1 subjects undergoing HCV treatment. Non‐responders had significantly higher baseline expression and selective induction of ISG‐15 after IFN‐α treatment relative to participants with sustained virological response. High baseline levels of ISG‐15 were also associated with less induction of ISG with treatment. These results support a role for ISG‐15 as a prognostic indicator and resistance factor to IFN‐α. J. Med. Virol. 85: 959–963, 2013. © 2013 Wiley Periodicals, Inc.